A critical reflection on the technological development of deep brain stimulation (DBS) - Ineichen, Christian; Glannon, Walter; Temel, Yasin; Baumann, Christian R.; Sürücü, Oguzkan (Frontiers in Human Neuroscience, 2014)
Since the translational research findings of Benabid and colleagues, which partly led to their seminal paper regarding the treatment of mainly tremor-dominant Parkinson patients through thalamic high-frequency-stimulation (HFS) in 1987, we still struggle with identifying a satisfactory mechanistic explanation of the underlying principles of Deep Brain Stimulation. Furthermore, the technological advance of DBS devices (electrodes and implantable pulse generators, IPG's) has shown a distinct lack of dynamic progression. In light of this we argue that it is time to leave the paleolithic age and enter hellenistic times: the device-manufacturing industry and the medical community together should put more emphasis on advancing the technology rather than resting on their laurels.